Benchmarking, a inovação como forma de conquistar clientes - SILVA, Bryan Rodrigues da; GONZAGA, Gustavo Marques; OLIVEIRA, Marcos Vinicius Gomes de; OLIVEIRA, Renan Ferraz Nunes de; PEREIRA, Wellington Fernandes; ARAÚJO, Wesley Alves Bezerra de (199, 2016)
Não tem
Benchmarking, innovation as a way to win customers
Keywords: Benchmarking; Inovação; Serviço ao cliente; Gestão e Negócios